CALCULATION METHOD OF AEROTECHNICS PRODUCTS FATIQUE STRENGTH SUBJECT TO CYCLIC LOADING - Pogrebniak, Anatolii; Regulskii, Mikhail; Yurchenko, Elena; Tugarinov, Aleksandr (Proceedings of National Aviation University (archive), 2014)
This article considers calculation method of structural strength coefficient, that ensures the requiredserviceability. The special emphasis is placed on limiting stress evaluation when structures are subject to multi-cycleasymmetric loading. The suggested approach enables to evaluate proof strength more correctly within the designprocess.